Effectiveness Test Of Anti-Acne Emulsigel Preparation Based On Clove Leaf Oil (Syzygium Aromaticum (L.) Merr & Perry) - Yoan Dasawanti; Candrika Candrika; Khaira Banu (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Acne is a common skin problem caused by the accumulation of oil that blocks the hair follicles. Factors contributing to acne include bacterial colonization by Staphylococcus epidermidis and Propionibacterium acnes, increased sebum production, and follicle disturbances. Generally, acne treatment aims to reduce sebum production, address inflammation, decrease bacterial colonization, and improve skin conditions. The commonly used therapies include antibiotics and retinoids, although challenges such as antibiotic resistance and side effects exist. As an alternative, clove (Syzygium aromaticum) contains eugenol, which has antibacterial properties that are effective against the growth of Propionibacterium acnes. A combination of emulsion and gel (emulsisponge) can be a stable and effective formulation for acne treatment. This study aimed to formulate clove leaf oil into an emulsified gel preparation, evaluate the formulation, and test its antibacterial activity. The study began with distillation of clove leaf oil and its formulation into an emulsion gel. Evaluation of the emulsion included organoleptic, homogeneity, pH, viscosity, particle size, skin irritation, and antibacterial activity tests. The results showed that The emulsified gel was white, aromatic, thick, and homogeneous. The emulsion has pH (4.5-6.5), viscosity (6500-9500 mPa.s), and particle size (8.3-14.1 µm), and remains stable for 12 weeks at room temperature, low temperature, and high temperature, without causing skin irritation. Antibacterial test results indicated that the emulsion exhibited a highly active inhibition zone.